2019
DOI: 10.1111/nep.13663
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and subclinical acute kidney injury in multidrug‐resistant septic patients treated with colistimethate sodium: Incidence and clinical outcomes

Abstract: Aim Colistimethate sodium (CMS) has been postulated as the principal cause of high incidence of clinical acute kidney injury (AKI) in multidrug‐resistance (MDR) septic patients with normal baseline serum creatinine (sCr) who were treated with CMS. This prospective observational study was conducted to examine the incidence and clinical outcomes of clinical and subclinical AKI in MDR septic patients receiving CMS. Methods Forty‐two MDR septic patients with normal sCr who required CMS were included. Clinical AKI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In contrast, Moledina et al coined the term 'hemodynamic AKI' (here 'clinical AKI') to describe a serum creatinine increase in the absence of increased kidney biomarker concentration, as may occur in cardiorenal syndrome or with renin-angiotensin-aldosterone system inhibition [19]. Recently, several original studies have used urinary biomarkers to define AKI subtypes in different patient populations including the Emergency Department, critical care and cardiac settings [3][4][5][6][7][8][9]. For example, Albert et al reported on NGAL and AKI consensus criteria-based AKI subtypes including subclinical (21.1%), clinical (4.5%) and combined AKI (7.5%) in patients following cardiac surgery [5].…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Moledina et al coined the term 'hemodynamic AKI' (here 'clinical AKI') to describe a serum creatinine increase in the absence of increased kidney biomarker concentration, as may occur in cardiorenal syndrome or with renin-angiotensin-aldosterone system inhibition [19]. Recently, several original studies have used urinary biomarkers to define AKI subtypes in different patient populations including the Emergency Department, critical care and cardiac settings [3][4][5][6][7][8][9]. For example, Albert et al reported on NGAL and AKI consensus criteria-based AKI subtypes including subclinical (21.1%), clinical (4.5%) and combined AKI (7.5%) in patients following cardiac surgery [5].…”
Section: Key Findingsmentioning
confidence: 99%
“…Recently, however, serum creatinine-independent kidney biomarkers have been investigated to help improve AKI diagnosis and prognosis. The combination of classical renal function parameters with biomarker levels, e.g., kidney injury molecule-1, interleukin 6, midkine and neutrophil gelatinase-associated lipocalin (NGAL), has led to the introduction of the concept of biomarker-based subtypes of AKI [3][4][5][6][7][8][9]. Some of these biomarkers may be particularly relevant to cardiac surgery patients undergoing cardiopulmonary bypass.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have described higher incidence of acute kidney injury (AKI) in patients treated with colistin, but most have small sample sizes, are not population-based, or study only one type of GNI [ 5 , 6 ]. AKI occurs in approximately 25–50% of patients treated with colistin [ 7 10 ], but has been reported as high as 90% in certain patients [ 11 ]. Those with comorbid conditions, including existing kidney disease, have increased risk of AKI while receiving colistin [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%